Successful school leadership preparation and development - Sanzo, Karen L.; Myran, Steve; Normore, Anthony H. (Emerald, 2012)
This book will feature lessons learned about the successful implementation of leadership program preparation and development programs that are grant-funded by the United States Department of Education through the School Leadership Program. Each chapter will highlight one or more practices that have been identified as a best practice by the literature and detail how the program implemented the practice(s). It is clear from the literature what should be done to prepare aspiring and current leaders (i.e. mentoring, in-depth internships, partnerships) but what is not clear is how to do this. This book will do exactly that with real-life experiences in the implementation of these practices (including successes, challenges, etc.). These will be authentic examples from the field about how practitioners have addressed challenges in implemented successful activities such as coaching, the internship, evaluating projects, and forging partnerships with preparation entities.
Includes indexes.
Keywords: Education -- Leadership.; Education -- Administration -- General.; Organization & management of education.; Schools.; School administrators -- Training of -- United States.; Educational leadership -- Study and teaching -- United States.; School management and organization -- Study and teaching -- United States.; elektronické knihy; electronic books